MANUSIA DAN PENDIDIKAN MENURUT AL-QUR’ÂN - Irman Majid (An-Nida', 2012)
Al-Qur’an as instructions which Allah revealed to Prophet Muhammad, to regulate of human life in this world this live up to the end of it its creation. There are two objectives that the creation of man by God, that is serve or worship for him, and be a caliph in the earth. In other hand is dealing with God as a creator. Humans are ‘abid or servants. While dealing with nature, human is the caliph or a person who was given a mandate by God to manage. Both of human fungtion must be done well, needs to know depth meaning of the two functions, the serve must be understood as a basic human duty with the understanding that all of actions or human tasks must be addressed to seek pleasure of Allah. The manage and prosper earth is it the worship. In the other words the earth must be managed as well as that no damges incurred. In order for the task performing as well as accordance with the mandate given by God to humans required sufficient knowlodge about the concept of devotion and the caliphate. Serve without science means making it uo or act of heresy. While, manage without the knowledge of the earth will cause damage and destruction which would be detrimental to human. To obtain reliable scientific required education, because of education is the planting of science and values as the efforts of teaching, habituation, guiedance, supervision and potential development in order to achieve harmony and perfection living in the world and the hereafter.